SUSTAINABILITY OF MICRO, SMALL, AND MEDIUM CULINARY ENTERPRISES IN THE DIGITAL MARKETING ERA BASED ON THE BUSINESS MODEL CANVAS (BMC) - Ahmad Maulana Ziharuddin; Aries Kurniawan; Putra Panji Respati; Beni Dwi Komara; Tsabita Kwarazmita (LPPM UNIVERSITAS BINA INSAN, 2026)
Objective: To analyze the business model of culinary Micro, Small, and Medium Enterprises (MSMEs) in Gresik Regency using nine elements of the Business Model Canvas (BMC). Research Methodology: This study was conducted in Sidayu District and involved four specific culinary MSME brands: Iwan Degan & Es Teler, Kebab Bintang, Pentol Gresik, and Wakul Tengah Sawah. This study used a qualitative approach with a phenomenological research type. Data were collected through interviews and observations, using the Business Model Canvas (BMC) as the primary analytical framework. Results: The study found that the most prominent business model elements are customer segments (dominated by students, workers, and local residents), value proposition (affordable prices, quality, and taste), revenue streams (core product sales), key resources (experience, workforce, skills), and core activities (production, sales, promotion). However, the channel and customer relationship elements are not optimally utilized; marketing is limited to simple digital media (WhatsApp, Facebook, Instagram, TikTok, GoFood), and relationships rely on direct communication without a structured loyalty program. Conclusion: Although the business model currently implemented by culinary MSMEs supports business sustainability, there is a significant need to strengthen channel elements and customer relationships to increase competitiveness and facilitate business development in the digital era. Limitations: This study is limited by its small sample size, focusing only on four culinary MSMEs in one district (Sidayu), which may affect the generalizability of the findings to a wider population of MSMEs. Contribution: This study contributes to the disciplines of business management and entrepreneurship by providing empirical evidence on the application of the Business Model Canvas in the culinary sector. It offers practical guidance for MSME owners in optimizing digital marketing channels and customer relationship management to ensure long-term sustainability